Effects of a nurse-led motor function rehabilitation training program for patients with ischemic stroke and family caregivers: study protocol for a randomized controlled trial - Yue Ding; Juan Xu; Qian-Yu Liang; Jia-Qi Zheng; Feng Wang; Ying Lin; Di-Ya Wang; Jing Su (Trials, 2024)
Abstract Background Both individuals and society bear a considerable burden from ischemic stroke (IS), not only do patients continue suffering from motor dysfunction after discharge from hospital, but their caregivers also undertake the principal responsibility of assisting them in reintegrating into the family and society. To better improve the IS patients’ limb function and daily life activities, their caregivers should also be involved in the training of the motor function rehabilitation during the period transitioning from hospital back home. This study mainly aims to investigate the effects of a nurse-led training for IS patients and their family caregivers on the improvement of the patients’ physical function and the burden of caregivers. Methods/design A randomized controlled trial with blind assessment will be conducted in hospitals and during the follow-ups at home. Fifty-eight pairs of adults diagnosed with ischemic stroke and their primary caregivers will be included. Participants will be randomly given with (1) a nurse-led, home-based motor rehabilitation training participated by caregivers (intervention group) or (2) routine self-care (control group). Both groups will receive assessment and health guidance on the day of discharge, and the intervention group will receive an additional home-based training program and supervision. These two groups will be followed up every week after discharge. The primary results are drawn from the evaluation of physical function and caregiver-related burden, and the secondary results derived from statistics of the modified Barthel index, stroke-specific quality of life, and National Institutes of Health Stroke Scale. Differences between the two groups will be measured by two-way repeated measures ANOVA, considering the data at baseline and at 1-week and 4-week follow-up after training. Discussion Results may provide novel and valuable information on the effects of this culturally appropriate, caregiver-involved, and home-based rehabilitation training on the physical function of IS patients and caregiver-related burden. Trial registration Chinese Clinical Trial Registry (chictr.org.cn) ChiCTR2300078798. Registered on December 19, 2023.